Heritability and Genetic Advance Estimates from the Parental Lines of Hybrid Maize (Zea Mays L.) - Biswas, T; Islam, MS; Methela, NJ (Journal of Environmental Science and Natural Resources, 2021)
Twenty-two genotypes of maize parental line were grown during 2017-2018 at the Research field of Plant Breeding Division, Regional Agricultural Research Station (RARS), Bangladesh Agricultural Research Institute (BARI), Rahmatpur, Barisal, Bangladesh. The experiment was laid out in randomized complete block design with three replications. Heritabilty, coefficients of variability and genetic advance values were computed for days to tasseling, days to silking, days to maturity, plant height (cm), ear height (cm), cob length (cm) and diameter (cm), number of seed rows per cob, number of seeds per row, number of seeds per cob, thousand grain weight (g) and yield (g/plant). Among all the traits higher phenotypic coefficient of variation (44.53) and genotypic coefficient of variation (44.18) were observed for yield/plant. The uppermost heritability was observed in case of yield per plant (98.41) followed by 1000 seed weight (96.91). Genetic advance was highest for seeds/cob (197.87) followed by 1000-kernel weight (176.86).Greater magnitude of heritability coupled with higher genetic advance in characters under study provided the evidence that these plant parameters were under the control of additive genetic effects. Indicating that selection should lead to a fast genetic improvement of the material. Environ. Sci. & Natural Resources, 12(1&2): 33-36, 2019